Persepsi Masyarakat Kota Pekanbaru Tehadap Gangguan Hama Permukiman - Agus Sutikno; Alim Arsyad; Bintal Amin; Radith Mahatma (JIP ( Jurnal Industri dan Perkotaan ), 2020)
Settlement pests are animals around humans and their settlements that cause physical and psychological disturbances to residents of the house. Its existence causes harm, loss and disturbance. Pests that are often a problem at home are mosquitoes, rats, cockroaches, and flies. Very few people tolerate the presence of pests in the house, even the only signs of their presence have led people to take control measures with pesticides. This research is a descriptive research that is to explain, detail and make a description of a symptom or object under study. The target population is households residing in Pekanbaru City, namely in the Districts of Tenayan Raya, Sail and Pekanbaru Kota. The sample was determined purposively with a multistage sampling technique. The research area is residential in Pekanbaru City with three categories of clean, medium and dirty. The data obtained were nominal, ordinal and ratio analysis. The relationship between data and quantitative data was analyzed using the chi-square test. The results showed that more than half of the respondents (95.88%) stated that there were residential pests in their houses. The most mosquitoes were found and felt by the residents of the house the most disturbing, so that the mosquitoes were the most controlled. As many as 41.44% of respondents thought that disturbance from pests was causing discomfort. In addition, people are very worried about contracting diseases carried by pests, especially dengue fever.